Two Factor Authentication Framework Using OTP-SMS Based on Blockchain - Alharbi, Eman; Alghazzawi, Daniyal (Transactions on Engineering and Computing Sciences, 2019)
The authentication process is the main step which should be used to confirm that the user is the legitimate one and give the access only for him. Recently, Two Factor Authentication (2FA) schemes have been used by most of the applications to add an extra layer of security on the login process and solve the vulnerabilities of using only one factor for authentication. OTP-SMS is one of the most common methods which has been used in 2FA. However, attackers found a way to attack this method and gain an access to the user’s account without their permission. In this paper, we proposed a new 2FA framework for OTP-SMS method to prevent different attacks, mainly Man In The Middle (MITM) attack and third party attack. The proposed framework is based on the use of Blockchain technology, which add more security and better environment for authentication process. The proposed framework uses an encrypted OTP, which generated by smart contract and uses also its hash value to send it to the application/website to complete the authentication process. We introduced a comparison between our proposed framework and other two frameworks which uses Blockchain to secure OTP-SMS. Our framework found to be secure against MITM and third party attacks and the computation time and complexity are less than other frameworks.